2010
DOI: 10.1111/j.1365-2044.2010.06310.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the prophylactic anti‐emetic efficacy of ramosetron and ondansetron in patients at high‐risk for postoperative nausea and vomiting after total knee replacement

Abstract: SummaryWe compared the prophylactic anti-emetic efficacy of ramosetron, a newly developed 5-HT 3 antagonist, and ondansetron in patients at high-risk for postoperative nausea and vomiting after total knee replacement. Eighty-four patients with three risk factors for postoperative nausea and vomiting (female, non-smoking and use of postoperative opioid use (ropivacaine and hydromorphone patient controlled epidural analgesia)) undergoing unilateral total knee replacement were randomly allocated to ramosetron 0.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
55
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 25 publications
10
55
1
Order By: Relevance
“…Our findings concur with those of previous studies showing the superior antiemetic effect of concurrent dexamethasone and 5-HT3 antagonist to the 5-HT3 antagonist alone [21,22], but no previous study has investigated the antiemetic efficacy of concomitant dexamethasone and ramosetron after TKA. Two previous studies reported that ramosetron monoprophylaxis after TKA provided a limited antiemetic effect during the 2-to 48-hour or 6-to 48-hour period compared with ondansetron or no prophylaxis [20,27]. Our findings, together with those of previous studies, suggest that prophylaxis with concomitant dexamethasone and ramosetron has a potent antiemetic effect on early PONV which is not provided by ramosetron alone.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Our findings concur with those of previous studies showing the superior antiemetic effect of concurrent dexamethasone and 5-HT3 antagonist to the 5-HT3 antagonist alone [21,22], but no previous study has investigated the antiemetic efficacy of concomitant dexamethasone and ramosetron after TKA. Two previous studies reported that ramosetron monoprophylaxis after TKA provided a limited antiemetic effect during the 2-to 48-hour or 6-to 48-hour period compared with ondansetron or no prophylaxis [20,27]. Our findings, together with those of previous studies, suggest that prophylaxis with concomitant dexamethasone and ramosetron has a potent antiemetic effect on early PONV which is not provided by ramosetron alone.…”
Section: Discussionsupporting
confidence: 70%
“…However, as a TKA involves extensive bone resection and soft tissue manipulation, patients can experience severe pain during the early postoperative period [13,42,[47][48][49]. Furthermore, many patients experience postoperative nausea and vomiting (PONV) after TKA, owing to not only anesthesia and surgery but also the various agents used for pain control [8,10,20,27]. Inadequate management of postoperative pain and PONV can lead to several systemic complications and delays recovery [13,16,34,48].…”
Section: Introductionmentioning
confidence: 99%
“…Hahm et al demonstrated that ramosetron 0.3 mg administered IV 30 min before the end of surgery was more effective than ondansetron 4 mg for preventing PONV during 0-24 h after anesthesia in 84 women undergoing total knee replacement. The incidence was 18% with ramosetron and 36% with ondansetron [27]. By contrast, ramosetron 0.3 mg administered IV at the end of surgery was as effective as ondansetron 8 mg, and both were more effective than placebo (P < 0.05) for the prevention of PONV during 0-24 h after anesthesia in 162 women undergoing gynecological surgery (PONV: 50% with ramosetron, 44% with ondansetron, and 69% with placebo) [28] and 120 patients (39 men and 41 women) undergoing laparoscopic cholecystectomy (PONV: 10% with ramosetron and 10% with ondansetron) [29].…”
Section: Prevention Of Ponv With Ramosetron In Adults (Table 1)mentioning
confidence: 96%
“…Recently, three comparative studies have evaluated the antiemetic efficacy of ramosetron and ondansetron in patients at high risk for PONV [27][28][29]. Hahm et al demonstrated that ramosetron 0.3 mg administered IV 30 min before the end of surgery was more effective than ondansetron 4 mg for preventing PONV during 0-24 h after anesthesia in 84 women undergoing total knee replacement.…”
Section: Prevention Of Ponv With Ramosetron In Adults (Table 1)mentioning
confidence: 99%
See 1 more Smart Citation